THE EFFECT OF LEADERSHIP STYLE, WORK ENVIRONMENT, AND ORGANIZATIONAL MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS VARIABLE MEDIATING - Defina Sulastiningtiyas; B Medina Nilasari (Business and Entrepreneurial Review, 2018)
This study is to examine the influence of leadership style, work environment, and organizational motivation on employee performance which is job satisfaction as mediating variable. The methodology of this study was hypotheses testing. Analytical technique used in testing the hypothesis is by Structural Equation Modelling (SEM) Method using Lisrel 8.80 software. A survey questionnaire was developed and validated. A total 124 questionnaire were distributed to Insurance’s agent PT. Askrindo Mitra Utama in Jakarta and 124 valid responses collected. The result from this study indicates that Leadership Style, Work Environment, Organizational Motivation has a positive and significant effect on Job Satisfaction; Leadership Style, and Organizational Motivation have a positive and significant effect on Employee Performance; but Work Environment does not have a positive and significant effect on Employee Performance; and there is a mediating effect of Job Satisfaction that can increase the influence of Leadership Style, Work Environment, and Organizational Motivation on Employee Performance.